Impact of the COVID-19 pandemic on the work of clinical psychologists in Austria: results of a mixed-methods study - Santillan-Ramos, Paola; Humer, Elke; Schaffler, Yvonne; Pieh, Christoph; Probst, Thomas; Felnhofer, Anna; Kothgassner, Oswald; Netzer, Ingeborg; Jesser, Andrea (Frontiers in Psychology, 2024)
Introduction Clinical psychologists in Austria shouldered a large part of the massive increase in demand for mental health services caused by the COVID-19 pandemic. This study aimed to find out how the pandemic affected their work and to gather information on how best to support the profession in the event of a crisis. Methods N = 172 Austrian clinical psychologists participated in a cross-sectional online survey between 11 April 2022 and 31 May 2022, including both closed and open-ended questions about their work. Open-ended questions were analyzed using qualitative content analysis. A mixed-methods analysis was conducted to test correlations between the categories derived from the qualitative analysis and professional variables. Results The analyses revealed that clinical psychologists, especially those with more years of experience, perceived an increased need for clinical psychological treatment, especially for children and adolescents, a lack of coverage for clinical psychological treatment by health insurance, a change to remote treatment formats, and a number of burdens associated with complying with COVID-19 measures. Discussion Clinical psychologists reported an urgent need to increase resources in both outpatient and inpatient settings and to promote health insurance coverage. To support the clinical psychology profession in providing high-quality work in times of crisis, there is a need to facilitate more opportunities for team and peer exchange, as well as financial support in the event of loss of income.